Analysis of Civic Education Learning in The Effort to Internalize The Local Wisdom of North Sulawesi - Pangalila, Theodorus; Sumilat, Juliana Margareta; Sobon, Kosmas (Technium Social Sciences Journal, 2021)
The purpose of this study is to describe the learning process of Civic Education in schools and identify the values of local wisdom of the people of North Sulawesi that can be used as a source in Civic Education learning at the elementary, junior high, and high school levels. This research focuses on identifying the values of local wisdom of the people of North Sulawesi and analyzing the level of need for developing a Civic Education model based on the local culture of the people of North Sulawesi. This study uses a qualitative approach. Sources of data from this study were teachers at the elementary, junior high, and high school levels in North Sulawesi. St. Catholic Elementary School Clara Tomohon, St. Don Bosco Catholic 2 Elementary School Paniki Bawah, SD Negeri 2 Tataaran, SMP Negeri 4 Tomohon, SMP Negeri 6 Manado, SMP Negeri 1 Tondano, SMK Negeri 1 Tomohon, SMA Negeri 1 Manado, and SMA Negeri 3 Tondano. Sources of data in this study were teachers who were in schools that were used as research locations. Collecting data through a google form, interview, observation, and literature study. Data analysis used the Miles and Huberman technique, namely data collection, data reduction, conclusion, and drawing/verification. In testing the validity of the data, the researcher will use internal validity (credibility) on the aspect of truth value in its application in terms of external validity (transferability) and reliability (dependability) on the consistency aspect and objectivity ( confirmability ) on the naturalist aspect. This study found that the teacher prepared the Civics learning process from the planning, implementing, and evaluating. There is an urgent need to develop Civics learning models based on the local wisdom of the people of North Sulawesi.